Faktor-Faktor yang Mempengaruhi Dividend Payout Ratio pada Perusahaan Manufaktur Periode 2009 - 2011 - Fazulul Arofah; Anton Anton (Jurnal Ilmiah Aset, 2014)
This study aimed to identify and analyze the factors that influence the dividend payout ratio of manufacturing companies in Indonesia. The population was 349 companies listed in Indonesia Stock Exchange, while the samples used were 25 companies. The technique was non-probability sampling with purposive sampling method judgment. The analysis tool used was multiple linear regression analysis method which also used classical assumption test. The results showed that the current ratio, debt to equity, and net profit margin did not affect the dividend payout ratio while the return on investment had significant positive effect. Current ratio, debt to equity, net profit margin, and return on investment simultaneously affected 11.8% dividend payout ratio while the remaining 88.2% were explained by other causes outside the model.